Factors influencing strategy execution in the South African petroleum industry - Mabece, Zwelakhe (My University, 2015)
South Africa (SA) produces, imports, and consumes the largest share of liquid fuels in Africa. A majority of SA’s fuels exports are destined to neighbouring economies. The SA petroleum industry has great strategic importance to the economy as a source of scarce jobs for people, businesses opportunities and government income. Its influence extends beyond economic boundaries to society and the physical environment. It is tightly regulated, yet a safe investment market as its regulatory framework guarantees companies reasonable investment returns. The purpose of this study was to identify the factors influencing strategy execution in the South African petroleum industry. The outcomes could contribute towards effective management of the factors that influence strategy execution of companies in the industry. A survey was conducted that consisted of 12 factor statements suggested by the literature review and that could influence strategy execution. Respondents from International Oil Companies, National Oil Companies, Wholesalers, Retailers and Service Providers were asked to ‘force rank’ a total of 100 points across one or all the factors. The survey also contained an open-ended question section to capture factors not covered the literature. All the factors that were recorded in literature and assessed in surveys were found to influence strategy execution, although at varying degrees across industry players. At an industry level the top 5 ranking factors were Leadership Skills; Regulatory Uncertainty; Strategy Clarity; Competencies and Environmental Concerns. The study also found from the open questions 3 new factors that could influence strategy execution. Leaders face the challenge of making impactful interventions during strategy execution. This study hopes to focus the attention of the leaders, managers and new entrants of the SA petroleum industry to the presented factors that greatly influence strategy execution in their companies.
Keywords: Strategic planning -- South Africa. Petroleum industry and trade -- South Africa.